Potensi Ekstrak Tanin Daun dan Kulit Batang Surian sebagai Penghambat α-Glukosidase (Tannin Extract Potential of Surian Leafand Bark as α-Glucosidase Inhibitor) - Fitriana S Monisa; Maria Bintang; Mega Safithri; Syamsul Falah (Masyarakat Peneliti Kayu Indonesia, 2016)
The purpose of the study was to know the inhibition activity surian leaves and bark tannin to α-glucosidase by in vitro method. Leaves and bark of surian was extracted with water and ethanol 70% solvent using infundation and maceration methods. Tannin was tested with phytochemical analysis and activity of inhibition to α-glucosidase with a microplate reader at a wavelength of 410 nm. The yield of tannins extract from leaves sample were 65.46% and 66.12% by water and ethanol 70% solvents, respectively, as well as 83.34% and 90.29% were obtained from bark sample. Water and ethanol extract of surian leaves and bark contain flavonoids, triterpenoids, tannins and saponins. Leaves tannin consist mainly hydrolyzable tannin, i.e. galat and gallotanin/ellagotanin, however, bark tannin consist of condensed tannin (catechol). Total tannin content of ethanol and water extract were 9.35 and 7.61 mg g-1 for bark sample, and 6.24 and 5.20 mg g-1 for leaves sample. Inhibition activity test showed that ethanol extract of leaves sample exhibited the highest inhibition activity (IC50=50.44 μg ml-1) and water extract of leaves sample was smallest (IC50=183.22 μg ml-1).